2011
DOI: 10.1080/02827581.2011.573502
|View full text |Cite
|
Sign up to set email alerts
|

Pine and spruce stump harvesting productivity and costs using a Pallari KH 160 stump-lifting tool

Abstract: Even though stumpwood may become a significant part of the future fuel mix for combined heat and power plants in Sweden the harvesting of stumps after regeneration fellings is still only performed on a trial basis. Results from time studies on two, 23 tonne, excavators fitted for stump lifting; together with followup data on stump lifting and forwarding are presented. Lifting, splitting and piling the stumps accounted for 17 %, 32 % and 32 %, respectively, of the total productive work time. A predictive model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
0
14
2
Order By: Relevance
“…The size of material was relatively large comparing to the study materials of earlier lifting studies (e.g. von Hofsten and Nordén 2007, Karlsson 2007, Hedman 2008, Laitila et al 2008, Jouhiaho and Mutikainen 2010, Jouhiaho et al 2010, Laitila 2010, Athanassiadis et al 2011, Erkkilä et al 2011. The study data was collected from only one excavator, which operated only one driver in two time study stands located in easy terrain.…”
Section: Discussion and Conlusionsmentioning
confidence: 89%
See 3 more Smart Citations
“…The size of material was relatively large comparing to the study materials of earlier lifting studies (e.g. von Hofsten and Nordén 2007, Karlsson 2007, Hedman 2008, Laitila et al 2008, Jouhiaho and Mutikainen 2010, Jouhiaho et al 2010, Laitila 2010, Athanassiadis et al 2011, Erkkilä et al 2011. The study data was collected from only one excavator, which operated only one driver in two time study stands located in easy terrain.…”
Section: Discussion and Conlusionsmentioning
confidence: 89%
“…Recent stump-lifting studies have demonstrated that the productivity of pine stump lifting is lower than in spruce stump lifting (e.g. Karlsson 2007, Hedman 2008, Lazdiņš et al 2009, Jouhiaho and Mutikainen 2010, Athanassiadis et al 2011, Erkkilä et al 2011.…”
Section: Discussion and Conlusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…To get stump parts clear of soil particles and stones, shaking of each piece is needed after it has been lifted above the ground level. On the research basis of this technology the figures on the productive work time distribution show that 17 % of the work time has been spent for lifting, 32 % -to split stumps, and the same amount of time -to put the stumps into a stack [6]. Created in Latvia prototype of the stump-lifting bucket MCR500 encompasses both an apparatus for stump uprooting and a device for soil scarification before forest planting.…”
Section: Introductionmentioning
confidence: 99%